2006
DOI: 10.1007/s00441-006-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

Collagen synthesis of articular cartilage explants in response to frequency of cyclic mechanical loading

Abstract: Articular cartilage in vivo experiences the effects of both cell-regulatory proteins and mechanical forces. This study has addressed the hypothesis that the frequency of intermittently or continuously applied mechanical loads is a critical parameter in the regulation of chondrocyte collagen biosynthesis. Cyclic compressive pressure was applied intermittently to bovine articular cartilage explants by using a sinusoidal waveform of 0.1-1.0 Hz frequency with a peak stress of 0.5 MPa for a period of 5-20 s followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…In line with the unaffected COL2A1 levels that we report herein, Wolf et al . reported that the rate of COL2A1 synthesis is unaffected by intermitted mechanical loading in cartilage explants (Wolf et al ., 2007). As mentioned, SOX9 expression was higher following loading at 0.05 MPa for 30 min than under unloaded conditions (fourfold; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the unaffected COL2A1 levels that we report herein, Wolf et al . reported that the rate of COL2A1 synthesis is unaffected by intermitted mechanical loading in cartilage explants (Wolf et al ., 2007). As mentioned, SOX9 expression was higher following loading at 0.05 MPa for 30 min than under unloaded conditions (fourfold; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These mechanical stimuli are important factors in the maintenance of normal structure and function of the articular cartilage. Periodic mechanical stress, as a special type of mechanical stimulation, can be used to advantage to simulate in vivo physiological mechanical conditions, enhancing the quality of tissue-engineered cartilage by promoting chondrocyte proliferation, migration, and matrix synthesis, which plays an important role in the repair of articular cartilage injury (2)(3)(4)(5). However, the mechanisms involved in chondrocytes to detect and respond to periodic mechanical stress have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In our quantitative protein analysis, we found that the protein level of type I collagen, which is always present in fibrocartilage, was significantly suppressed, while the protein level of type II collagen required in articular cartilage showed no significant change after periodic mechanical stress [31]. Not only was type I collagen reduced, but type III, type V, type VI and other related collagens which are closely connected to fibrosis were also decreased after periodic mechanical stress.…”
Section: Discussionmentioning
confidence: 99%